Macaronesian Muscidae (Diptera). IV. The genus Helina Robineau-Desvoidy, and description of the male of Spilogona maderensis Michelsen - Michelsen, Verner (Zootaxa, 2023)
The Macaronesian species of the muscid genus Helina are revised. The genus is represented in the Canary Islands by 9 species, in Madeira by 7 species, and in the Azores Islands by 1 species. Four species, one divided in two subspecies, are endemic to the Canary Islands: Helina grancanariae sp. nov. (Gran Canaria), H. obscurisquama obscurisquama (Stein) (Tenerife, La Gomera), H. obscurisquama pseudonivalis (Santos Abréu) ssp. rev. (La Palma), H. rufitibialis Hennig (Tenerife, La Gomera, La Palma) and H. santosabreui sp. nov. (La Gomera, La Palma). The following three species are endemic to Madeira: Helina atlantica (Tiensuu), H. lundbladi Tiensuu and H. vilissima Hennig. Existing records of Helina almeriensis (Strobl) and H. quadrum (Fabricius) from the Canary Islands are considered as misidentifications. An identification key to males and females concludes the species accounts. Finally, a description is given of the previously unknown male sex of the endemic Madeiran Spilogona maderensis Michelsen.